Experimental investigation on performance and emission characteristics of moringa seed oil biodiesel with added ethanol in CI engine. (2022) - Jegadheesan, C.; Somasundaram, P.; Devaprasanth, E.; Sasikumar, Suganth; Suriyaprasanth, L.; Pal Singh, Ajit; Jeyaprakash, N.
Abstract: Global petroleum requirements for running diesel engines is increasing, while petro-diesel reliability is deteriorating, resulting in high diesel prices as well as other negative consequences of igniting hydrocarbon-based diesel in engine, such as air pollution and global warming. Biodiesel is a more environmentally friendly alternative to petro-diesel. The biodiesel made of Moringa seed oil (MSO) and Ethanol could be appropriate interchange fuel, as it is sustainable with higher energy efficiency. The MSO biodiesel produced from moringa seed by trans-esterification of the unrefined MSO + methanol within the sight of NaOH as reactive catalyst makes it reasonable to be mixed with diesel. B5 (950 ml Diesel + 45 ml MSO + 5 ml Ethanol) and B10 (900 ml Diesel + 90 ml MSO + 10 ml Ethanol) blends are made with 90 percent MSO and 10% Ethanol. In this study, a variable compression ratio is employed to conduct performance and emission testing using the three fuel options mentioned above, and the brake thermal efficiency of the B5 blend gives 11.18 percent to 16.54 percent better characteristics than diesel fuel.